Hematological and antioxidants responses of dairy cow fed with a combination of feed and duckweed (Lemna minor) as a mixture for improving milk biosynthesis: The effects of feed duckweed - Ujang Hidayat Tanuwiria; Andi Mushawwir (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Tanuwiria UH, Mushawwir A. 2020. Hematological and antioxidants responses of dairy cows fed with a combination of feed and duckweed (Lemna minor) as a mixture for improving performance. Biodiversitas 21: 4741-4746. A total of twenty-five, 5-7th-lactation-old or 7-8thyears-old dairy cows were used in the current study to study the effect of feed duckweed (Lemna minor) on the hematological status and parameters related antioxidant in the dairy cow. Each group of treatment involved 5 replicates with a dairy cow each (5 dairy cows per group). All of the group was provided ration following F0 = Uncultivated grass (UG) 60% and supplemented concentrated (C) 40%; F1 = UG 50%+fresh  duckweed 10%+C 40%; F2 = UG 60%+fresh  duckweed 3%+C 37%; F3 = UG 50%+fresh  duckweed 10%+dried  duckweed  3%+C 37%; F4 = UG 45%+fresh  duckweed 15%+dried  duckweed  2%+C 38%. Blood samples were collected from each dairy cow monthly beginning at the first month of this experiment, from the tail vein (vena coccygeal), using a sterilized syringe and vacuum tube containing K3EDTA. Hematological parameters were analyzed by a hematology analyzer. The blood samples collected were also centrifuged to separate the plasma. The plasma was used to determine of concentration of parameters related to antioxidant by an automatic biochemical analyzer, using a commercial kit. All procedure of the analysis was following based on the Biolabo kit (Franch) and Randox kit (UK). Based on in this current study showed that increased hematological condition and antioxidants profile in dairy cow supplemented duckweed . Supplemented duckweed  can be improved physiological condition (hematologic and antioxidants) in the dairy cow.